EFEKTIVITAS TEMUAN FRAUD AUDIT, TINDAK LANJUT HASIL PEMERIKSAAN DAN OPINI AUDIT OLEH BPK DALAM MEMPENGARUHI TINGKAT KORUPSI PADA PROVINSI DI PULAU JAWA PERIODE TAHUN 2015 - 2019 - Mauristela Mauristela; Haryanto Haryanto (Diponegoro Journal of Accounting, 2022)
This study aims to analyze the effect of findings and follow-up on the results of BPK's examination on the level of corruption and the number of audit findings in the Financial Statements of Provincial Governments in Java. This study uses panel data with a sample of 6 provinces on the island of Java which indicate that there is corruption handled by the Corruption Eradication Commission (KPK) during the period 2015-2019. The results showed that the number of audit findings and audit opinion did not affect the level of corruption, but the follow-up on the results of the examination had a negative effect which could be stated if the Provincial Government followed up on the results of the examination by the BPK, indicating that there is seriousness from the Provincial Government to reduce the number of corruption crimes in Indonesia. the province. Efforts to make improvements in accordance with the auditor's recommendations need to be continuously improved by the Provincial Government because it can significantly reduce the level of corruption.